(untitled) (Eurasian Journal of Engineering and Technology, 2025)
This study focuses on the analysis of Land Surface Temperature (LST) and Normalized Difference Moisture Index (NDMI) in Zomin National Park for August 2021, using Sentinel-2 satellite imagery. The study aims to assess the spatiotemporal variations in LST and NDMI, providing insights into the environmental conditions and vegetation health of the park. Sentinel-2 data was processed to extract both LST and NDMI, which were then analyzed to observe the relationship between temperature fluctuations and vegetation moisture content. The results highlight the seasonal dynamics of the park’s ecosystem, contributing to the understanding of climate change impacts and vegetation stress. This research offers valuable information for monitoring and managing the park’s natural resources.